THE IMPACT OF TEAM GAMES TOURNAMENT WITH READING INFUSION TOWARDS THE IMPROVEMENT OF STUDENTS' LEARNING ACTIVITIES AND ACHIEVEMENT IN WAVES TOPIC - Nuraeni, Fitri (2013)
As one of alternative solution for the lack of activities and low achievement in science learning, Team Games Tournament (TGT) with reading infusion is implemented through pre experiment research with one group pretest posttest design in which the samples are fourteen low-achiever-students in secondary-2 level in one of private school in Bandung who are chosen through availability sampling. It is found that after the lesson has been conducted there is medium improvement of students' achievement as the average normalized gain value is 0.43. The highest improvement is in remembering (C1) domain and the lowest improvement is in applying (C3) domain. Moreover, students' activities also improve in the second cycle of lesson implementation, which is seen from the increasing percentage of students who did visual, oral, motor and writing activities that promote learning. The implementation of TGT with reading infusion also give positive impact toward the learning interaction among students, where symmetric interaction more likely appear on the second cycle of lesson implementation. Yet, the implementation of reading infusion is still very poor where according to questionnaire result it is found that most of the students did not want to read the science text because they want teacher explain the concept later and most of them taught that reading science text before coming to science lesson is useless. Keywords: Team Games Tournament (TGT), Reading infusion, Learning activity Learning achievement, Waves topic